Investigations in two-dimensional arithmetic geometry - Morrow, Matthew Thomas (2009)
This thesis explores a variety of topics in two-dimensional arithmetic geometry, including the further development of I. Fesenko's adelic analysis and its relations with ramification theory, model-theoretic integration on valued fields, and Grothendieck duality on arithmetic surfaces.